Automatic Detection and Classification of Human Emotion in Real-Time Scenario - Keshri, Ashish; Singh, Ayush; Kumar, Baibhav; Pratap, Devenrdra; Chauhan, Ankit (Journal of ISMAC, 2022)
This work proposes the implementation of the idea of real-time human emotion recognition through digital image processing techniques using CNN. This work presents significant literacy calculations used in facial protestation for exact distinctive verification and acknowledgment that can effectively and capably see sentiments from the vibes of the client. The proposed model gives six probability values based on six different expressions. Large datasets are explored and investigated for training facial emotion recognition model. In support of this work, CNN using Deep learning model, OpenCV, Tensorflow, Keras, Pandas, and Numpy is used for digital computer vision procedures involved, and an lite experiment is conducted for various men and women of different age, race, and colour to descry their feelings and variations for different faces are found. This work is improved in 3 targets as face location, acknowledgment and feeling arrangement. Open CV library, and facial expression images dataset are used in this proposed work. Also python writing computer programs is utilized for computer vision (using webcam) procedures. To demonstrate ongoing adequacy, an investigation is directed for a very long time to distinguish their internal feelings and track down physiological changes for each face. The consequences of the examinations exhibit the idealizations in face investigation framework. At long last, the exhibition of programmed face detection and recognition are measured with very high accuracy and in real-time. This method can be implemented and is widely useful in various domains such as security, schools, colleges and universities, military, airlines, banking etc.
Keywords: CNN; Deep learning model; Face emotion recognition